The Effect of Problem-based Learning on Students Collaboration Skills in Islamic Boarding Schools - Ufiqurrohman, Ufiqurrohman; Antika, Linda Tri (Lombok Institute, 2023)
Collaboration skills are one of the skills required to be developed in 21st-century education. This study aimed to determine the effect of implementing the problem-based learning (PBL) model on the collaboration skills of Islamic boarding school students. This research is a quasi-experimental study using a non-equivalent pretest-posttest control group design. This research was conducted at MA Miftahul Ulum Bettet Pamekasan, even semester of the 2021/2022 academic year. Collaboration skills data was collected through observation sheets and then analyzed using the t-test to determine differences in collaboration skills in the control and experimental group. The results showed that the implementation of PBL in learning could improve the collaboration skills of Islamic boarding school students (Sig. <.05). The results of this study indicate that the PBL learning model can be used as a reference for learning models to develop students' collaboration skills.